Ok, its been a while (working on a major java program project) anyways for this proof this is what i did using your advice:
t[sub:gnsvgfd7]a[/sub:gnsvgfd7](x) t[sub:gnsvgfd7]a[/sub:gnsvgfd7](y)=(ax[sup:gnsvgfd7]-1[/sup:gnsvgfd7]a)(aya[sup:gnsvgfd7]-1[/sup:gnsvgfd7])
=axya[sup:gnsvgfd7]-1[/sup:gnsvgfd7]
=t[sub:gnsvgfd7]a[/sub:gnsvgfd7](xy)
so the operation is preserved.
Onto:
Let x exist in G, then a[sup:gnsvgfd7]-1[/sup:gnsvgfd7]xa exists in G, and t[sub:gnsvgfd7]a[/sub:gnsvgfd7](a[sup:gnsvgfd7]-1[/sup:gnsvgfd7]xa)=a(a[sup:gnsvgfd7]-1[/sup:gnsvgfd7]xa)a[sup:gnsvgfd7]-1[/sup:gnsvgfd7]
after reassociating: =(aa[sup:gnsvgfd7]-1[/sup:gnsvgfd7])x(aa[sup:gnsvgfd7]-1[/sup:gnsvgfd7])=x, therefore it is onto
One-to-One:
Let t[sub:gnsvgfd7]a[/sub:gnsvgfd7](x[sub:gnsvgfd7]1[/sub:gnsvgfd7])=t[sub:gnsvgfd7]a[/sub:gnsvgfd7](x[sub:gnsvgfd7]2[/sub:gnsvgfd7]). Now show that x[sub:gnsvgfd7]1[/sub:gnsvgfd7]=x[sub:gnsvgfd7]2[/sub:gnsvgfd7].
well t[sub:gnsvgfd7]a[/sub:gnsvgfd7](x[sub:gnsvgfd7]1[/sub:gnsvgfd7])=t[sub:gnsvgfd7]a[/sub:gnsvgfd7](x[sub:gnsvgfd7]2[/sub:gnsvgfd7]) implies that ax[sub:gnsvgfd7]1[/sub:gnsvgfd7]a[sup:gnsvgfd7]-1[/sup:gnsvgfd7]=ax[sub:gnsvgfd7]2[/sub:gnsvgfd7]a[sup:gnsvgfd7]-1[/sup:gnsvgfd7], which implies that x[sub:gnsvgfd7]1[/sub:gnsvgfd7]=x[sub:gnsvgfd7]2[/sub:gnsvgfd7], after some multiplying by a[sup:gnsvgfd7]-1[/sup:gnsvgfd7] in the back and a in the front.
therefore it is one-to-one
and since all three requirements are met t[sub:gnsvgfd7]a[/sub:gnsvgfd7] is an automorphism